Enriching English Vocabulary and Literacy of The Children Through Digital Resources - Rini Susilowati (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Children need exposure when they learn English vocabulary. The more exposure of the target language they receive, the more words they obtain. The rich vocabulary the children have will help them to do better English literacy which support them to convey the message that they read. Children need learning variation both at school and at home to diminish boredom and enhance their learning interest toward English. Learning English with their teachers at school using printed material, pictures, and objects surround them is a daily thing they do in the class. Children need different learning activity to experience something new which can refresh their mind so it can maintain their learning motivation. This article will elaborate how children can learn differently from the common thing they do in which learning through digital resources. Learning through digital tools and using digital resources is a distinct option nowadays. A lot of digital resources can be explored by English teachers as well as children’s parent to be used as learning tool. Various kind of digital stories can be chosen to improve children’s English literacy. Meanwhile, teachers and parent can also browse a lot of digital vocabulary learning activities such as digital video with various topics, memory vocabulary game, concentration vocabulary game, digital flashcard, vocabulary puzzles with various topics and other digital vocabulary learning activities. Those digital vocabulary resources having interesting visual, color and material which can create an enjoyable and playful leaning atmosphere. Therefore, using digital resources in the attempt to enrich English vocabulary and literacy of the children can be applied to make learning variation.